Expression of the epithelial sodium channel (ENaC) in the endometrium – Implications for fertility in a patient with pseudohypoaldosteronism. Issue 183 (October 2018) - Boggula, Vijay R.; Hanukoglu, Israel; Sagiv, Ron; Enuka, Yehoshua; Hanukoglu, Aaron
Graphical abstract: Highlights: In healthy women, ENaC is localized in the apical membrane of the uterine epithelia. A patient with pseudohypoaldosteronism could not conceive despite repeated IVF treatments. In her endometrial Pipelle biopsy samples, ENaC could hardly be detected on the apical membrane. These findings support the hypothesis that ENaC expression in the endometrium is crucial for implantation. Abstract: Pseudohypoaldosteronism type 1 (PHA) is a syndrome of unresponsiveness to aldosterone. The severe form of this disease results from mutations in the genes that encode for the epithelial sodium channel subunits, SCNN1A, SCNN1B, and SCNN1G. A PHA patient under our care failed to conceive after many years and IVF trials. Our earlier studies had shown that ENaC is expressed in the female reproductive tract. We hypothesized that a defective ENaC expression may be responsible for the infertility of the patient. To test this hypothesis we examined ENaC expression in endometrial Pipelle biopsy samples from three healthy women and the PHA patient with an Arg508X mutation in the SCNN1A gene. The formalin fixed samples were reacted with anti-ENaCA (alpha subunit) antisera, followed by secondary antibodies to visualize ENaC expression by immunofluorescence. Confocal microscopy imaging of the samples showed strong ENaC immunofluorescence along the luminal border (apical membrane) of the epithelial cells in Pipelle samples from healthy women. In contrast, none of the samples from the PHA patient showed ENaC immunofluorescence. The Arg508X mutation interrupts the transport of ENaC subunits to the cell surface, yet it would not be expected to disrupt ENaC localization in the cytoplasm. In contrast to endometrium where ENaC is localized in the apical membrane of the epithelial cells, in keratinocytes ENaC is expressed in cytoplasmic pools. Therefore, we examined ENaC immunofluorescence in plucked hair follicles. As expected, ENaC immunofluorescence was detected in the cytoplasm of keratinocytes of both normal and PHA samples. Our results support the hypothesis that lack of expression of ENaC on the endometrial surface may be responsible for the infertility of the PHA patient.